Analisis Faktor Lingkungan Fisik dan Faktor Individu Terhadap Kejadian Stres Kerja Pada Pekerja Industri Cor Aluminium “WL” di Yogyakarta - Carissa Riskiananda; Mohammad Mirza Fauzie; Narto Narto (Poltekkes Kemenkes Yogyakarta, 2014)
Job stress is an early stage of the occurrence of a disease in individuals whose susceptible and may lead to psychosomatical, neurotical and psychosical disturbance that can be indicated by the increa-sing number of absentiisme, late for work, employement changing, work accident and the magnitude of company loss due to the absence of workers. A preliminary survey conducted in aluminium indus-try “WL’” in Yogyakarta City, revealed that most workers were experiencing job stress in moderate level and showed some complaints. The aim of this study is to understand the relationship between physical factors in work environment, which consisted of temperature, humidity, illumination, and noise; and age and working time of workers, with job stress incidence among that factory’s workers. The study was an observational analytical type with crosssectional survey design approached. The study population was all workers in the production section of the industry, and the subsequent 30 sample workers were obtained by using simple random sampling technique. The job stress were measured twice by HARS questionnaire, i.e. 15 minutes before and after working hour, meanwhile the measurement of physical condition was conducted during the working hours. The discrepancy between pre-test and post-test stress score mesurement were analysed to find out it’s relationship with all the independet variables by using correlation test at 95 % level of confidence. The results showed that the all six factors under study were significantly related with job stress, as follows: tem-perature (r=0,655; p<0,001), humidity (r=0,349; p=0,029), illumination (r=0,426, p= 0,009), noise (r= 0,327; p=0,039), age(r=0,418; p=0,011), and working time (r=0,329; p=0,038).